(untitled) (Web of Teachers: Inderscience Research, 2025)
This article extensively covers general concepts of watercolor technique, as well as its possibilities for artistic expression in fine arts. The role of watercolor art in developing aesthetic taste, patience, observation skills, and emotional expression in students is emphasized.